Synthesis and biological evaluation of fluoro-substituted spiro-isoxazolines as potential anti-viral and anti-cancer agents. Issue 50 (17th August 2020) - Das, Prasanta; Boone, Sarah; Mitra, Dipanwita; Turner, Lindsay; Tandon, Ritesh; Raucher, Drazen; Hamme, Ashton T.
Abstract : The synthetic efficacy and biological relevance extend an opportunity to further drug-discovery development of fluoro-spiro-isoxazolines as novel anti-viral and anti-cancer agents. Abstract : Electrophilic fluorine-mediated dearomative spirocyclization has been developed to synthesize a range of fluoro-substituted spiro-isoxazoline ethers and lactones. The in vitro biological assays of synthesized compounds were probed for anti-viral activity against human cytomegalovirus (HCMV) and cytotoxicity against glioblastomas (GBM6) and triple negative breast cancer (MDA MB 231). Interestingly, compounds 4d and 4n showed significant activity against HCMV (IC50 ∼ 10 μM), while 4l and 5f revealed the highest cytotoxicity with IC50 = 36 to 80 μM. The synthetic efficacy and biological relevance offer an opportunity to further drug-discovery development of fluoro-spiro-isoxazolines as novel anti-viral and anti-cancer agents.